Francisco de Quevedo. Poeta i filozof polityczny - Śrama, Marcin (Dialogi Polityczne, 2021)
Francisco de Quevedo (1580–1645) was Spanish nobleman, politician, writer and political thinker. His most important political works are La política de Dios, y gobierno de Cristo (1626; eng. “The Politics of the Lord”) and La vida de Marco Bruto (1644; eng. “The Life of Marcus Brutus”). De Quevedo described his political thing in these letters in which he emphasized the role of the ruler’s responsibility. De Quevedo dealt with the issue of admissibility of resistance to power and tyrannicide when the king does not fulfill his duties. Also, following the example of saint Thomas Aquinas, he saw in the king a follower of Christ. For this reason, Jesus’s deeds were the basis for his reflection.